Oxidative stress and TB outcomes in patients with diabetes mellitus?. (15th February 2017) - Yew, Wing Wai; Leung, Chi Chiu; Zhang, Ying
Abstract : In patients with diabetes mellitus, TB treatment outcomes are poorer. Most parameters, when measured, reflect the slower bacteriological conversion from positivity to negativity and higher risks of disease relapse and mortality, as well as a greater propensity to develop drug-resistant TB. Aside from the well-known immunological dysfunction inherent to patients with diabetes mellitus, oxidative stress is likely a major underlying mechanism adversely impacting their TB treatment outcomes. Mycobacterium tuberculosis persisters, formed as a result of the core dormancy response to stress, possibly play a central role in this hypothesis. This hypothetical model also underscores the paramount importance of programmatic management of TB and diabetes mellitus, in collaboration, to improve the outcomes of patients with both diseases. The validity of these ideas could be further ascertained by laboratory and clinical research.